1993
DOI: 10.1176/ajp.150.11.1731
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and platelet excitatory amino acids in psychiatric disorders

Abstract: Plasma and platelet levels of excitatory amino acids were measured in 38 psychiatric out-patients and in 19 comparison subjects; the patients had DSM-III-R diagnoses of organic mental disorders (N = 3), mood disorders (N = 15), schizophrenia (N = 13), and anxiety disorders (N = 7). The glutamate plasma levels were significantly higher in the patients with mood disorders than in the comparison group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(37 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…The result is compatible with previous reports, which showed increased serum levels of glutamate in chronic schizophrenia patients 28, 29 . A couple of reports have attempted and failed to replicate these findings 30, 31 ; however, a recent meta-analysis confirmed that the peripheral glutamate level of schizophrenia subjects was significantly higher than that of HC 24 . While these are findings pertain to chronic schizophrenia, we found increased glutamate levels in FEP.…”
Section: Discussionmentioning
confidence: 99%
“…The result is compatible with previous reports, which showed increased serum levels of glutamate in chronic schizophrenia patients 28, 29 . A couple of reports have attempted and failed to replicate these findings 30, 31 ; however, a recent meta-analysis confirmed that the peripheral glutamate level of schizophrenia subjects was significantly higher than that of HC 24 . While these are findings pertain to chronic schizophrenia, we found increased glutamate levels in FEP.…”
Section: Discussionmentioning
confidence: 99%
“…Patients on second-generation antipsychotics were found to be more responsive to external cues for eating and they felt less satiated after a meal than patients who were not on second-generation antipsychotics [34]. In this meta-analysis, only four out of the 13 studies put patients on a controlled diet, thus dietary differences between patient and controls groups should be taken into consideration [17,26,27,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Overall, 3 studies used the diagnostic criteria of the DSM-III-R [11,19,35], 2 studies used the diagnostic criteria of the DSM-IV [25,36] and 1 study used the diagnostic criteria of the Research Diagnostic Criteria by Schneider [17]. Schneider's Research Diagnostic Criteria is only available in German and could not be reviewed for this analysis; four studies did not report the diagnostic criteria used [4,16,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Increased activity of the glutamatergic system in the peripheral blood of depressive patients has been repeatedly shown [69,70,71], although this result could not be replicated by all groups [72]. The inconsistency of the findings, however, might be due to methodological problems [73].…”
Section: Inflammation Influences the Metabolism Of Serotonin And Noramentioning
confidence: 99%